2022
DOI: 10.1007/s10856-022-06685-0
|View full text |Cite
|
Sign up to set email alerts
|

Repair of critical diaphyseal defects of lower limbs by 3D printed porous Ti6Al4V scaffolds without additional bone grafting: a prospective clinical study

Abstract: The repair of critical diaphyseal defects of lower weight-bearing limbs is an intractable problem in clinical practice. From December 2017, we prospectively applied 3D printed porous Ti6Al4V scaffolds to reconstruct this kind of bone defect. All patients experienced a two-stage surgical process, including thorough debridement and scaffold implantation. With an average follow-up of 23.0 months, ten patients with 11 parts of bone defects were enrolled in this study. The case series included three females and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Apart from physical injuries, bacterial infections in bone (osteomyelitis), caused by pathogens including Morganella morganii , Staphylococcus hemolyticus , Staphylococcus aureus, Pseudomonas aeruginosa, and Enterobacter cloacae , cause bone defects majorly located at the femur, which can cause serious health issues. A clinical study conducted by Liu’s team reported that, in ten patients with femur and tibia defects (osteomylities), serial postoperative radiologic follow-ups showed a substantial process and results in bone developing and remodeling around the implanted Ti6Al4V scaffold . They also reported on the impact and effectiveness of therapeutic procedures in clinical applications, particularly for patients with osteomyelitis and nonunion with poor osseous and vascular integrity, to rebuild significant damaged bone tissue of legs and feet without further bone marrow transplants.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from physical injuries, bacterial infections in bone (osteomyelitis), caused by pathogens including Morganella morganii , Staphylococcus hemolyticus , Staphylococcus aureus, Pseudomonas aeruginosa, and Enterobacter cloacae , cause bone defects majorly located at the femur, which can cause serious health issues. A clinical study conducted by Liu’s team reported that, in ten patients with femur and tibia defects (osteomylities), serial postoperative radiologic follow-ups showed a substantial process and results in bone developing and remodeling around the implanted Ti6Al4V scaffold . They also reported on the impact and effectiveness of therapeutic procedures in clinical applications, particularly for patients with osteomyelitis and nonunion with poor osseous and vascular integrity, to rebuild significant damaged bone tissue of legs and feet without further bone marrow transplants.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…A clinical study conducted by Liu's team reported that, in ten patients with femur and tibia defects (osteomylities), serial postoperative radiologic follow-ups showed a substantial process and results in bone developing and remodeling around the implanted Ti6Al4V scaffold. 195 They also reported on the impact and effectiveness of therapeutic procedures in clinical applications, particularly for patients with osteomyelitis and nonunion with poor osseous and vascular integrity, to rebuild significant damaged bone tissue of legs and feet without further bone marrow transplants. The balance mechanism of load-bearing limbs with critical defects, whether early functional training and load-bearing could be accomplished as well as required to meet conditions, is examined in configurations and properties of new bone regeneration in vital diaphyseal bone damage of lower limbs treated by this proposed method (Figure 9).…”
Section: Preclinical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the emergence of three-dimensional (3D) printing technology, personalized and precise repair and reconstruction are no longer out of reach. In a prospective study, Liu et al [ 100 ] reported using the 3D-printed porous Ti6Al4V scaffolds to repair critical diaphyseal defects of the lower limbs and achieved satisfying postoperative functions and low complication rates.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, an idea appeared to fill bone defects with a personalized titanium implants, the design of which (inner cells and pores) is similar to the structure of spongy bone [ 10 , 11 , 12 ]. Experimental studies demonstrated that osseointegration of such an implant provides fast and durable restoration of a bone defect, but the titanium does not allow monitoring the process of reparative bone regeneration and its functional restructuring in clinical conditions by the methods of X-rays [ 13 , 14 , 15 ]. Furthermore, sometimes a metal implant remained into the bone arises concerns of a patient.…”
Section: Introductionmentioning
confidence: 99%